Hillenbrand seals Abel Pumps purchase. Issue 10 (October 2015) - Unknown
Abstract : Hillenbrand Inc has completed its acquisition of Abel Pumps LP and certain of its affiliates in a €95 million cash deal (see Pump Industry Analyst, September 2015).